HUBUNGAN ANTARA PRIMIGRAVIDA DENGAN ANGKA KEJADIAN PREEKLAMSIA/EKLAMSIA DI RS ISLAM SAMARINDA - Irfan; Arsyad (Jurnal Kebidanan Mutiara Mahakam, 2016)
In Indonesia, maternal mortality rate were 307/100.000 life labor. Preeclampsia/eclampsia is one of the major cause of perinatal morbidity and mortality. Incidence rate of preeclampsia/eclampsia raised because on primigravida stress are common when having a labor.The purpose of this study was to know and to analyze the correlation between primigravida with the incidence rate of preeclampsia/eclampsia.This study was analytic survey with cross sectional approach. Method of this study is using purposive sampling. The number of sample were 120 pregnant women which was get from medical reports in RS Islam Samarinda period 2015. The data was analyzed by chi square by using SPSS 15 program.From the chi square statistic analyze, we got X2 = 4,304, the probability (p) = 0,045 and prevalense ratio (RP = 1,458). It was mean primigravida had more chance, it was about 1,458 to get preeclampsia/eclampsia than the women was not primigravida.The conclusion was there was the correlation between primigravida with the incidence rate of preeclampsia/eclampsia (there was a significant correlation between pimigravida with the incidence rate of preeclampsia /eclampsia).